The immunological characteristics of TSPAN1 expressing B cells in autoimmune hepatitis - Ou, Yiyan; Chen, Ruiling; Qian, Qiwei; Cui, Nana; Miao, Qi; Tang, Ruqi; You, Zhengrui; Ma, Xiong; Wang, Qixia (Frontiers in Immunology, 2022)
Background and aims Tetraspanin proteins are closely related to the functional changes of B cells, including antigen presentation, production of cytokines, and transduction. We aim to explore the potential role of Tetraspanin 1 (TSPAN1) in the biological activities of B cells in AIH. Methods and results Herein, this study found that numbers of cells expressing TSPAN1 were significantly increased in AIH patients compared to PBC, chronic hepatitis B, and healthy control (P < 0.0001). Moreover, there was a positive correlation between numbers of TSPAN1+ cells and AIH disease severity (P < 0.0001). Immunofluorescence staining further confirmed that TSPAN1 was primarily expressed on CD19+ B cells. Flow-cytometric analysis showed that TSPAN1+ B cells secreted more inflammatory cytokines and expressed higher level of CD86 than TSPAN1- B cells. Furthermore, compared with TSAPN1- cells, the expression of CXCR3 on TSPAN1+ cells was also higher. Meanwhile, CXCL10, the ligand of CXCR3, was significantly elevated in the liver of AIH (P < 0.01) and had positive correlation with the quantities of TSPAN1 (P < 0.05). Interestingly, the numbers of TSPAN1+ B cells were decreased in AIH patients after immunosuppressive therapy. Conclusions TSPAN1+ B cells in the liver may promote the progression of AIH via secreting cytokines and presenting antigens. The chemotactic movement of TSPAN1+ B cells toward the liver of AIH was possibly due to CXCR3 - CXCL10 interaction.